The characteristics, needs and individual experience of older forensic psychiatric patients: across-sectional study in three secure units within one regional service - Di Lorito, Claudio (2019)
Intro. Secure forensic psychiatric settings in the United Kingdom offer treatment to mentally-disordered offenders or non-offending patients who present a risk to themselves and others, given the severity or nature of their symptoms. In the last decade, several demographic, socio-cultural and legal factors have caused an increase in the prevalence of patients over 50 years, who currently represent around 20% of residents in forensic psychiatric settings in the UK. However, population growth has not been matched by research. With little to no evidence, it is therefore difficult to determine whether secure services are adequately addressing the individual needs of older patients.